Perturbed gut microbiota and serum metabolites are associated with progressive renal fibrosis - Wang, Run-Xi; Zhou, Hong-Bing; Gao, Jia-Xing; Li, Xing-Hua; Bai, Wan-Fu; Wang, Jia; Bai, Ying-Chun; Fan, Li-Ya; Chang, Hong; Shi, Song-Li (Frontiers in Medicine, 2025)
IntroductionThe intricate pathogenesis of renal fibrosis necessitates identifying biomarkers at various stages to facilitate targeted therapeutic interventions, which would enhance patient survival rates and significantly improve prognosis.MethodsWe investigated the changes in gut microbiota and serum metabolites during the early, middle, and late stages of renal fibrosis in rats using 16S rDNA sequencing and UPLC-QTOF/MS-based metabolomics.ResultsWe identified 5, 21, and 14 potential gut microbial markers and 19, 23, and 31 potential metabolic markers in the MOD1, MOD2, and MOD4 groups, respectively. Bifidobacterium was identified as a shared microbial marker between the MOD1 and MOD2 groups; Prevotellaceae_NK3B31_group and Bacteroides were identified as shared microbial markers between the MOD2 and MOD4 groups. The pathways of arachidonic acid metabolism and retinol metabolism were found to play a significant role in the modulation of renal fibrosis at 1, 2, and 4 weeks. Notably, the metabolic biomarkers 8,9-EET and 5(S)-HPETE within these pathways emerged as critical determinants influencing renal fibrosis.DiscussionOur findings demonstrated that the severity of renal fibrosis is associated with dysbiosis of the gut microbiota and alterations in serum metabolites.